A PROPÓSITO DE LA PRIVATIZACION DE PETRO PERU. Negocios Independientes o Integración Vertical - Roca, Santiago (1995)
It analyzes the various sales modalities raised in view of the privatization of the state oil company, Petroperú, mainly the modality of subdivision into independent businesses proposed by the Special Committee for the Promotion of Private Investment (Cepri) of this company. It finds that, apparently, the oil industry needs to operate vertically integrated; however, this possibility must be determined based on the market, the interlinking between the parties and the objectives to be achieved for the benefit of the country. On the other hand, the plan presented by Cepri combines transfer of ownership, strategic alliances with oil operators, concession and license mechanisms, but it would also establish the obligatory of a series of long-term contracts and regulatory mechanisms that would replace the internal transactions of an integrated system. Other options that could generate positive results are also analyzed, provided the necessary regulations are in place. Finally, it points out that in order to decide the best form of privatization, not only the costs, risks and business potential of each option must be evaluated, but also the political consequences and the benefits that the State would obtain from each one of them.